Linking job work hours to women’s physical health: The role of perceived unfairness and household work hours - Thomas, Candice L.; Laguda, Emem; Olufemi-Ayoola, Folasade; Netzley, Stephen; Yu, Jia; Spitzmueller, Christiane (Sex Roles, 2018)
Although the relationship between job work hours and women’s physical health has been examined, limited empirical research examines the family demand conditions that explain this relationship. Given the challenge of integrating work and family demands, we examine the boundary conditions under which job hours relate to women’s physical health by integrating the influences of household work hours, perceived unfairness of division of household labor, and traditional gender ideology. Using a large, multi-national archival dataset, our results show that women working long job hours are more likely to report decreased physical health and that this relationship is moderated by the hours and fairness perceptions of household labor: The lowest physical health was observed at high job hours and high household hours and also when women felt that they did less than their fair share of household labor. However, looking at the slopes of these relationships, the negative relationship between job hours and physical health was stronger when women worked lower household hours or felt that they contributed less than their fair share of household labor—suggesting that maintaining a contribution to household labor might be important for working women. Furthermore, these results suggest that policy and organizational interventions aimed at supporting women’s physical health could take their household labor contributions and fairness perceptions into account when assessing the negative impact of high job work hours. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; conciliation famille-travail; culpabilité; discipline; division sexuelle du travail; famille; projet charge mentale; psychologie; psychologie sociale; périodes historiques; rapports sociaux de sexe; sciences humaines; thématiques; travail; travail domestique

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis